Costoclavicular block as a diaphragm-sparing nerve block for shoulder surgery: a randomized controlled trial - Youngin Lee; Seunguk Bang; Jihyun Chung; Min Suk Chae; Jungwon Shin (Korean Journal of Anesthesiology)
Background Distal nerve block approaches have been explored to reduce hemidiaphragmatic paresis (HDP) more effectively than interscalene block (ISB). However, these approaches are associated with a high incidence of HDP. The costoclavicular block (CCB) provides effective analgesia while reducing HDP. Here, we hypothesized that CCB would decrease the incidence of HDP compared to ISB while still providing effective pain relief after surgery. Methods Seventy patients who underwent arthroscopic rotator cuff repair were randomly allocated to receive either ultrasound-guided CCB (n = 35) or ISB (n = 35). Each group received 0.2% ropivacaine (20 ml CCB, 10 ml ISB). The primary outcome was the incidence of HDP, as measured using M-mode ultrasound. Diaphragmatic excursion, pulmonary function test results, opioid consumption, and pain scores were evaluated. Results Sixty-six patients were included. CCB group had a significantly lower incidence of HDP than those in the ISB group (5.9% vs. 84.4%, P < 0.001). The diaphragmatic excursion reduction was significantly more in the ISB (3.87 cm) group than in the CCB (0.25 cm) group (P < 0.001). The decrease in forced vital capacity and forced expiratory volume in 1 s from baseline was significantly greater in the ISB. There was no significant difference in opioid consumption between the two groups during the entire postoperative period. Conclusions Compared with ISB, CCB significantly reduced the incidence of HDP while maintaining effective analgesia and causing less pulmonary function impairment. CCB may be a viable option for diaphragmatic-sparing analgesia after shoulder surgery.